Pediatric multiple sclerosis – rare case of multiple sclerosis in an adolescent boy - Pragya Punj,; Eby P Baby,; Aniket Pratap Singh Jadon,; Sambita Panda,; P K Biswal, (Indian Journal of Child Health, 2021)
Multiple sclerosis (MS) is a chronic inflammatory, demyelinating neurodegenerative, and autoimmune disorder of the central nervous system of unknown etiology. The peak onset is between age 20 and 40 years and it usually affects more women than men. Although much knowledge has been achieved on the diagnosis and treatment of adult patients with MS, it remains a matter of debate and controversy in childhood. We present a case of MS in a 12-year-old-boy, review the current state of the knowledge on pediatric MS and discuss the available tools for the diagnosis and treatment.